Rationalism and the disembodiment of modern childbirth: The case for an ecology of childbirth - Viola, Federico Ignacio (2020)
The paper proposes a genealogy of the biomedical paradigm surrounding childbirth, with the aim of deconstructing the principles of rationalism that led to the objectification of the body and to the consequent commodification of birth. We intend to demonstrate how such a conception of the body and of sensibility determines the birth process, which leads us to consider it an event that is relational in nature. Methodologically, this deconstruction is carried out through a critical-descriptive genealogy of the theoretical assumptions of the rationalist conception of the body. By developing the concept of ecology of childbirth, we intend to call into question this relational nature of the body and to recover the value of corporeality and embodiment as a language of proximity, within a theoretical framework of the ethics of difference. This vindication of the ecologicalrelational nature of sensibility has the potential to establish a dynamic of responsibility and cooperation capable of subverting the rationalist logic of control and the dominion of the current biomedical paradigm.